Language and ideology in the media: Treatment of gender in news reports / Maziana Osman and Shazul Ezry - Osman, Maziana; Ezry, Shazul (2005)
Language encodes ideas and meanings and in doing so, brings along with it a particular world-view of the text producer. The present study attempts to investigate how media portray men and women, through the analysis of language use. Samples of news reports were collected from three media forms within a duration of one week. The findings showed that there was differential treatment as to how men and women were portrayed in the media.